Modeling of integrated signal converters for biomedical sensor microsystems - Kogut, I.T.; Dzundza, B.S.; Holota, V.I.; Bulbuk, O.I.; Fedoriuk, V.V.; Nykyruy, L.I. (Physics and Chemistry of Solid State, 2023)
The paper presents the results of computer modeling of the proposed functional-electrical circuit of integrated signal converters (ISC) from photosensitive elements based on CMOS operational amplifiers, which is intended for the construction of an element base of hybrid sensor microsystems for biomedical applications. A feature of this ISC is the regulation and filtering of the amplitude of the constant component in the amplified signal from the diode photosensitive element in the wave range of 400 - 1040 nm. Computer simulation of the functioning of the device was carried out, the constituent components were determined and their parametric optimization was carried out. The results of experimental studies and computer modeling agree well, which confirms the correct functioning of the proposed signal converter from photosensitive elements. The developed ISC is suitable for creating real devices, both on the basis of discrete components and in an integrated design, as an element of sensor microsystems-on-a-chip or intelligent sensors.